El espectro de las demencias frontotemporales - Donoso S., Archibaldo; González V., Rafael; Behrens P., María Isabel (Revista Hospital Clínico Universidad de Chile, 2009)
With the purpose of displaying the spectrum of frontotemporal dementias and associated disorders we present a series of patients with: frontotemporal dementia (frontal variant), progressive non-fluent aphasia, semantic dementia, apraxia of speech, and amyotrophic lateral sclerosis associated with frontotemporal dementia. In addition we present cases of corticobasal degeneration and progressive supranuclear palsy that may be considered in the frontotemporal dementia spectrum. The diagnostic difficulties, which require of semiologic expertise more than complementary exams, are underscored. On the other hand the necessity of neuropathologic confirmation is emphazised, since the clinical manifestations are not always in accordance with the autopsy features.